2017
DOI: 10.1007/s00595-017-1546-2
|View full text |Cite|
|
Sign up to set email alerts
|

Human CD200 suppresses macrophage-mediated xenogeneic cytotoxicity and phagocytosis

Abstract: Our findings indicate that human CD200 suppresses the xenogeneic rejection by CD200R macrophages and that the generation of hCD200 transgenic pigs for use in xenografts is very attractive for preventing the macrophage-mediated rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…In animal models, CD200/CD200R signaling prevents allograft rejection. [36] Yu et al [5] showed that CD200R positively stimulated DCs, modulated alloimmune tolerance, and reduced natural killer cell activity in transgenic mice overexpressing CD200. Moreover, enhanced interleukin 10 and TGF-β production through CD200R increased the chance of graft acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, CD200/CD200R signaling prevents allograft rejection. [36] Yu et al [5] showed that CD200R positively stimulated DCs, modulated alloimmune tolerance, and reduced natural killer cell activity in transgenic mice overexpressing CD200. Moreover, enhanced interleukin 10 and TGF-β production through CD200R increased the chance of graft acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…Various factors are related to macrophage activation: for example, activation by innate antibodies (Fcγ activation), IFN‐γ (by NK and Th1), and complement pathway (antibody‐independent pathway among the classical pathways, second pathway, and lectin pathway), and danger‐associated molecular pattern (DAMP)‐induced activation 17 . Among these, antibody‐independent complement pathway or DAMP‐induced macrophage activation is T/B/NK cell‐independent factors.…”
Section: Discussionmentioning
confidence: 99%
“…CD200 (OX-2 membrane glycoprotein) is a transmembrane protein that is typically expressed on the surface of hematopoietic-derived cells, as well as B-cells, activated T cells, endothelial cells and neuronal cells ( 262 ). Expression of CD200 on endothelial cells was found to inhibit phagocytosis of those cells by macrophages, possibly by engaging the CD200 receptor, CD200R ( 263 ). However, CD200 inhibits inflammation via CD200R ( 262 ), so it is possible that the inhibition of phagocytosis is indirect via inhibiting inflammation.…”
Section: The Phagocytic Codementioning
confidence: 99%